1992
DOI: 10.1111/j.1471-4159.1992.tb09340.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Neurochemical Evaluation of Striatal Serotonergic Hyperinnervation in Rats Depleted of Dopamine at Infancy

Abstract: Destruction of nigrostriatal dopamine (DA) neurons with 6-hydroxydopamine (6-OHDA) early in development results in hyperinnervation of striatum by the serotonergic afferents deriving from the dorsal raphe nucleus. We have used in vivo microdialysis to investigate the degree to which serotonergic neurotransmission in striatum is altered by this increase in the density of serotonin (5-HT) terminals. The effects of several manipulations known to influence 5-HT function on extracellular 5-HT and 5-hydroxyindoleace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 57 publications
1
17
1
Order By: Relevance
“…Interestingly, these lesions have also been reported to result in the sprouting of 5-HT terminals [49][50][51][52]. Therefore, it is possible that increased 5-HT neurotransmission in the developing striatum may elicit more drastic effects on neuropeptide gene expression as compared to the present study in which 5-HT was removed.…”
Section: Discussioncontrasting
confidence: 53%
“…Interestingly, these lesions have also been reported to result in the sprouting of 5-HT terminals [49][50][51][52]. Therefore, it is possible that increased 5-HT neurotransmission in the developing striatum may elicit more drastic effects on neuropeptide gene expression as compared to the present study in which 5-HT was removed.…”
Section: Discussioncontrasting
confidence: 53%
“…Because dialysate 5-HT is representative of the equilibrium between release and reuptake, inhibition of the latter resulted in lower increments of the 5-HT concentration in lesioned rats. An opposite situation (i.e., hyperinnervation of the striatum by 5-HT terminals in dopamine-depleted rats at infancy) also results in unchanged baseline 5-HT values but greater increments after blockade of the 5-HT reuptake (Jackson and Abercrombie, 1992). Hence, it appears that changes in the brain extracellular fraction of 5-HT take place only after the disruption of the balance between release and reuptake (e.g., by axonal depolarization or inactivation of the 5-HT transporter), despite the existence of an extensive lesion of the serotonergic system.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies indicated that, in absence of pharmacological interventions, the extracellular concentration of 5-HT in different areas of the rat brain is confined within a relatively narrow range and does not reflect that present in brain tissue Jackson and Abercrombie, 1992). In experiments involving destruction of the serotonergic system with 5,7-DHT, Daszuta et al (1989) reported a very severe reduction of basal dialysate 5-HT values in the VHPC of lesioned rats, whereas Kirby et al (1995) found unaltered dialysate 5-HT values even after an almost complete (Ͼ90%) lesion of the striatal 5-HT system.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, the phenoNeonatal cell death of nigrostriatal dopaminergic neurons produced by 6-hydroxydopamine administration type of transgenic mouse models could be a mere consequence of developmental abnormality, instead of resulted in serotonergic hyperinnervation of striatum from the dorsal raphe nucleus. 35 The serotonergic hypthe physiological role of a targeted gene product per se. Recent development of molecular genetic techniques erinnervation increased the capacity of 5-HT release by 3-fold in the striatum of the neonatally dopaminemakes it possible to circumvent this problem by spatiotemporal regulation of a gene-targeting or transgene depleted rat.…”
Section: Manipulation Of Neurotransmitter Inactivationmentioning
confidence: 99%